Heat tolerance of Zebu and Friesian-Zebu crosses in the Guinea savanna zone of Nigeria - Buvanendran, V.; Adamu, A.M.; Abubakar, B.Y. (1992)
Comparative evaluation of the zebu and crossbreds to heat tolerance were carried out over a period of 4 months. Physiological measurements of two indigenous zebu breeds of cattle, Bunaji (BU) and Sokoto Gudali (SG) and the half-crosses of Friesian-White Fulani (CB) were taken after exposure to field conditions. Rectal temperature did not differ between breeds but respiration rate and sweating rate were higher in the CB. Haematocrit and plasma protein did not differ significantly between breeds. The repeatability of respiration rate was therefore a more reliable physiological measure of response to climatic stress. The CB was less adapted than the zebu.